Characteristics of clinic discharge patients with SARS-Cov-2 hospitalized at EsSalud in the Lambayeque Region - Soto-Cáceres, Rosario Alexandra (2021)
Introduction. The Covid 19 pandemic has caused high lethality in the Lambayeque region, collapsing hospitals. Objectives: describe, by gender, the characteristics of clinic discharge patients with sars-cov2 hospitalized at EsSalud in the Lambayeque region. Material and Methods: Observational, retrospective, descriptive study, selecting a representative sample of confirmed COVID 19 cases between April 1 to June 30, 2020 at the Almanzor Aguinaga Asenjo National Hospital (HNAAA) and the Luis Heysen Inchaustegui Hospital (HLHI) ; as exclusion criteria: those with less than 48 hours of stay, the deceased and those referred to other establishments. The clinical history data were collected in the SGSS system, Excel software was used for data processing. Results: 329 patients were registered, of which 70% were male, mean age 55.9 +/- 11 years; Diagnosis was by serological test 80% and chest tomography 17%. Dyspnea was the predominant symptom 85%, lymphopenia 51% and high C-reactive protein 39% and high LDH 35%. Treatment was mainly oxygen 89% and enoxaparin 87%, azithromycin 86% and ceftriaxone 70%, hospital complications were ARDS 88.1% and atypical pneumonia 86.6%, hospital stay was 7.85 + / - 5.42 days. Conclusions: The majority of hospitalized in Essalud were men, average age 55.9 years; main symptom dyspnea; lymphopenia with high C-reactive protein and LDH predominated; the treatment was based on oxygen and enoxaparin, mean hospital stay of 7.85 days.